IMPACT OF GOVERNMENT INVESTMENT EXPENDITURE ON ECONOMIC GROWTH IN GHANA - Abdulai, A-M; Abubakari, A. (UDS International Journal of Development, 2022)
The paper investigated the impact of government investment expenditure on economic growth in Ghana using secondary data spanning from 1975 to 2018. The Autoregressive Distributed Lag (ARDL) and the Granger Causality test were adopted to examine the objectives. The results showed that government investment expenditure related positively to economic growth in the long run, but has no statistically significant effect on growth in the short run. Other variables such as foreign direct investment, labour force, gross capital formation, debt service, interest rate, inflation rate, and foreign aid influenced growth positively or negatively. A unidirectional causal relationship ran from Government investment expenditure to growth. The study, therefore, recommends that to attain sustainable future economic growth, the government should pay more attention to its investment expenditure; by providing the necessary resources and the enabling environment for education, health and technology. Keywords: Government Investment Expenditure, Growth, ARDL, Granger Causality, Human capital